Perceptions And Images of Women in the Social Media Environment as Factors Shaping Patterns of Social Interaction and Relations in Contemporary Society - Siti Wahdatul Alawiah; Dini Fitriani; Purnama Rika Perdana (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the evolving representation of women on social media and its influence on contemporary social interaction. As digital platforms increasingly shape public perception, social media has become a powerful space where images, narratives, and algorithm-driven content contribute to the construction of women’s identities in online environments. Using a qualitative descriptive approach, this research synthesizes 25 peer-reviewed journal articles published between 2020 and 2025, selected based on inclusion criteria that emphasize relevance to women’s representation, gender discourse, and social interaction within digital platforms. The selected studies focus on empirical and theoretical discussions of visual portrayals, online discourse, and algorithmic influence in social media contexts. The analysis explores how visual representations, patterns of engagement, and platform exposure affect gender relations and broader social behavior. The findings indicate that social media functions as a double-edged sphere. On one hand, it enhances women’s visibility, autonomy, and participation in public discourse, providing opportunities for self-expression, advocacy, and empowerment. On the other hand, it continues to reproduce restrictive gender norms through the circulation of idealized beauty standards, objectification, and the commodification of female identity. These representations significantly influence how audiences perceive and interact with women both online and offline. Furthermore, algorithmic systems often reinforce such portrayals by prioritizing content aligned with engagement-driven metrics, thereby perpetuating dominant stereotypes. Despite these challenges, digital platforms also facilitate the emergence of counter-narratives and supportive communities that challenge traditional gender roles. Overall, this study highlights the importance of digital media literacy and platform accountability in fostering more equitable, diverse, and inclusive representations of women in the digital age.